Solid-state synthesis of pure ye'elimite. Issue 9 (August 2018) - El Khessaimi, Y.; El Hafiane, Y.; Smith, A.; Trauchessec, R.; Diliberto, C.; Lecomte, A.
Abstract: Ye'elimite is formed during the production of sulfoaluminate cement. In this article, the orthorhombic ye'elimite formation, the optimal synthesis conditions and the microstructural evolution during synthesis, by solid-state reaction from pure oxide raw materials, is investigated. The phase assemblage was substantially affected by temperature and duration of sintering. Making reference to Rietveld quantitative analysis results, optimal solid-state synthesis conditions of ye'elimite was 1300 °C for 3 h. During ye'elimite synthesis, significant gas releases were observed at different stages of firing using TGA coupled with mass-spectrometer. The gases are the product of carbonate decomposition, gypsum dehydration and sulfate decomposition from the unreacted anhydrite and the formed ye'elimite. Based on the present work, it emerges that a key strategy for forming ye'elimite with a high purity is to compensate sulfate decomposition by the addition of a slight excess of CaSO4 before repeating the firing cycle at optimal conditions. Finally, the porosity was investigated using Archimedes principle measurements compared to BSE-image analysis. It shows the difficulty to achieve dense sintered ye'elimite because of the high decomposition gas releases during the firing process.